2018
DOI: 10.2217/crc-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

The New Trend in the Treatment of Experimental Cryptosporidiosis and the Resulting Intestinal Dysplasia

Abstract: Aim: Cryptosporidiosis causes colon dysplasia. This research aimed to evaluate the effect of a novel combination between artesunate and nitazoxanide on intensity of infection and the resulting intestinal dysplasia. Materials & methods: Subjects were divided into five groups. Artesunate was used alone, then combined with nitazoxanide. Results: The highest efficacy in reducing oocyst shedding obtained from the combined therapy (68.5, 75.9, 99%) after 7, 14 and 21 days. The histopathology of infected colonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
4
6
0
Order By: Relevance
“…However, adenocarcinoma development was not detected in this model, probably due to the early time of euthanasia. Similar observations were reported by others using the same mice model [60]. Moreover, the severity of the dysplastic lesions seemed to be correlated with the intensity of oocyst shedding [61].…”
Section: Natural or Experimental Infection In Animalssupporting
confidence: 89%
“…However, adenocarcinoma development was not detected in this model, probably due to the early time of euthanasia. Similar observations were reported by others using the same mice model [60]. Moreover, the severity of the dysplastic lesions seemed to be correlated with the intensity of oocyst shedding [61].…”
Section: Natural or Experimental Infection In Animalssupporting
confidence: 89%
“…In the present study, the immunocompromised mice were treated with combination of NTZ & piperazine citrate 30mg/kg for 7 days started a week post infection, with high significant reduction in C. parvum oocysts that was more or less similar to nitazoxanide treated mice. This agreed with Mostafa et al (2018) in Egypt who found that combination of artesunate and nanazoxide showed a synergistic effect by reducing number of C. parvum oocysts shed and improving dysplastic changes induced by cryptosporidiosis infection in the colon of immunosuppressed mice as compared to that induced by either artesunate or nanazoxide alone. Besides, Checkley et al (2018) in USA reported that diagnostic tests for Cryptosporidium infection were the suboptimum necessitating specialized tests must be often insensitive.…”
Section: Discussionsupporting
confidence: 89%
“…The pathological picture of examined ilium of different groups were in the form of Limited treatment options also pose a major challenge to public health, giving the significant burden of disease. Those finding come in agreement with [24] who stated that The histopathology of infected colonic mucosa showed marked improvement and low-grade of dysplasia in the infected and treated group with the combined therapy of (artesunate and…”
Section: Necrosis Of Cryptssupporting
confidence: 91%